Controlling the Photo-Degradation Rate Constant of PS Containing Nickel(II) Complex - Hussain , Zainab; Alsayed, Raghda; Alwash , Atheel; Ahmed , Ahmed; Noaman, Riyadh; H Jawad, Ali; Yousif , Emad (Al-Nahrain Journal of Science, 2019)
The complex of Ni(II) metal with 4-amino-5-(pyridyl)-4H-1,2,4-triazole-3-thiol was used as a polystyrene (PS) films photostabilizer. The PS films comprising concentrating of complex 0.5% wwere outputted by casting method from chloroform solvent. The photostabilization activities of PS films compounds with dissimilar thickness were identified by computing the photodegradation rate constant (kd) for blank and modified polystyrene. From the practical consequences obtained, a mechanism was proposed count on the installation of the complex. The PS films were irradiated utilizing a 365 nm wavelength light source with intensity 6.02 10-9 Ein dm-3 s-1 at room temperature.